High-strength self-assembly gel foam oil-displacing agent and preparation method thereof

By self-assembling gel foam oil repellent with high-strength self-assembly and using oil repellents composed of tereophilic hydrophobic copolymers, the problem of low recovery rate of carbonate rock-cavity reservoirs is solved, and the problem of low recovery rate of carbonate rock-cavity reservoirs is achieved. Efficient oil-water separation and improve recovery.

CN119432348AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202310939624.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-28
Publication Date
2025-02-14
Estimated Expiration
2043-07-28

AI Technical Summary

Technical Problem

The recovery rate of carbonate rock-cavity-type reservoirs is low. The existing water injection, gas injection and supporting efficiency enhancement technologies have problems with low water flooding efficiency and gas flooding risks, and a more effective oil flooding method is needed.

Method used

High-strength self-assembled gel foam oil repellent, which consists of terezophilic hydrophobic copolymers, zwitterionic surfactants, nonionic surfactants, heat-resistant polyacids and counterion compounds. It is composed of self-assembled through the interaction between quadruple molecules to form an ordered aggregate, which improves the viscosity of the bubble liquid and the stability of the foam.

Benefits of technology

Under high temperature and high salt conditions, the stability and sealing capacity of the foam are improved, the recovery rate is significantly improved, the oil-water interface tension is reduced, and the oil-washing efficiency is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004364719240000021
    Figure BDA0004364719240000021
  • Figure BDA0004364719240000061
    Figure BDA0004364719240000061
  • Figure BDA0004364719240000071
    Figure BDA0004364719240000071
Patent Text Reader

Abstract

The invention provides a high-strength self-assembly gel foam oil displacement agent and a preparation method thereof, and belongs to the field of chemical oil displacement. The high-strength self-assembly gel foam oil-displacing agent is prepared from the following components: a ternary amphiphilic hydrophobic association copolymer, a zwitterionic surfactant, a nonionic surfactant, heat-resistant polybasic acid, a counter-ion compound, a chelating agent and formation water. According to the self-assembly gel foam oil-displacing agent, quadruple interaction is formed among molecules of all the components, the strength of foaming liquid is remarkably improved, generated nitrogen foam is fine, rich and good in stability, large cracks and karst caves can be blocked in a fracture-cavity type oil reservoir, the swept volume can be effectively enlarged, the crude oil recovery rate of the fracture-cavity type oil reservoir can be remarkably increased, and the oil-displacing effect is good. The foaming agent does not generate precipitates with calcium and magnesium ions, and does not separate out due to salt.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical oil displacement, and in particular relates to a high-strength self-assembling gel foam oil displacement agent and a preparation method thereof. Background Art

[0002] Carbonate fracture-cave reservoirs have great resource potential. The karst patterns can be divided into surface weathering crust karst, fault-controlled karst and ancient dark river karst. The storage space is mainly large caves, large fractures and dissolution pores. The scales vary greatly, from micrometers to meters, with strong heterogeneity and generally low recovery rates. At present, the main methods to improve the recovery rate of carbonate fracture-cave reservoirs in Tahe are water injection, gas injection and supporting efficiency enhancement technologies. Since 60%-70% of the cave reservoirs have collapsed and the filling degree is high, the flow characteristics in the fracture development zone vary greatly, and the injected medium is easy to penetrate along the high-conductivity channel, resulting in low water drive efficiency. Nitrogen injection has a high risk of gas channeling. Therefore, it is necessary to find more effective methods and theoretical guidance to improve the recovery rate and further improve the recovery rate of carbonate fracture-cave reservoirs.

[0003] Based on the adjustment of nitrogen flooding channels, the purpose of optimizing the adjustment and adjustment is achieved by optimizing the supporting medium for nitrogen injection. Nitrogen foam is mainly used as the main adjustment medium. Foam has the characteristics of selective plugging, blocking large but not small, blocking water but not oil. These characteristics make foam flooding technology have great development prospects in oilfield development. By improving the oil-water interfacial tension and plugging the high channel of injected nitrogen migration, the crude oil recovery rate is further improved. As an inert gas, nitrogen is not easy to react with formation fluids and rocks, which is safe and economical. At the same time, it has low solubility in water, which reduces the adverse effects caused by emulsification and precipitation blockage. Therefore, testing nitrogen foam flooding can further enrich and develop the theory of improving the recovery rate of carbonate reservoirs, which has important theoretical and practical significance. Nitrogen foam flooding technology is a tertiary oil recovery technology based on nitrogen flooding and diversified oil displacement mechanism. With its unique properties and oil displacement mechanism, it has shown great advantages in the process of oil and gas field exploitation and has received widespread attention at home and abroad.

[0004] Aiming at the problem of poor gas flooding effect and adverse effects in carbonate fracture-vuggy reservoirs, a pilot test of gel foam flooding was carried out in the TK647 well in the Tahe Oilfield, which achieved initial results and verified the feasibility of foam flooding.

[0005] The gel foam system is subjected to ultra-high temperature of 140°C and 24×10 4The adaptability of the ultra-high salt reservoir of mg / L needs to be optimized. In the process of mine application, the long-term stability of the gel foam system (effective period of mine application) is not high enough. The gel foam system developed in the early stage involves a variety of agents in the formation process, and the system is relatively complex, resulting in increased use costs; in addition, the mine construction process of the gel foam system is slightly cumbersome and needs further optimization. The optimization of the system and the simplification of the process will definitely further improve the economic benefits of the mine application of the gel foam system.

[0006] In view of the above practical problems and characteristics of fracture-cavity oil reservoirs, after molecular structure design and repeated experiments, a high-strength self-assembled foam oil-displacing agent suitable for fracture-cavity oil reservoirs used in the present invention can form ordered aggregates through multiple self-assembly under high temperature and high salt conditions, effectively improve the viscosity of the foaming liquid, increase the thickness of the foam interface film, and effectively improve the stability of the foam. The formed foam has a longer stability time, the ability to seal cracks and caves is enhanced, and the expansion of the sweep efficiency is more significant. Summary of the invention

[0007] In view of the defects of the prior art, the present invention provides a high-strength self-assembled gel foam oil displacement agent suitable for fracture-cavity oil reservoirs and a preparation method thereof. The components of the raw materials can self-assemble to form ordered aggregates through quadruple intermolecular interactions, which greatly increases the viscosity of the foaming liquid under high temperature and high salt conditions. It has the characteristics of being alkali-free and non-corrosive, and has good temperature and salt resistance. It can make the oil-water interfacial tension reach an ultra-low value. The generated foam is fine, stable and rich. It can block large cracks and caves in fracture-cavity oil reservoirs, expand the affected volume, and significantly improve the recovery rate.

[0008] A high-strength self-assembled gel foam oil-displacing agent, comprising the following components in percentage by weight:

[0009]

[0010] The remainder is formation water.

[0011] The mineralization of the formation water is 100,000-300,000 mg / L.

[0012] Wherein, the ternary amphiphilic hydrophobically associating copolymer is obtained by copolymerization of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC);

[0013] The mass ratio of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS) and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC) monomer units in the ternary amphiphilic hydrophobically associating copolymer is 4-6:0.5-1:0.1-0.3.

[0014] The preparation method of the ternary amphiphilic hydrophobically associating copolymer is described in (Synthesis, Characterization and Property Research of Amphiphilic Water-Soluble Polymers, Kuang Wei, PhD Dissertation of Shandong University, 2013).

[0015] The zwitterionic surfactant is erucamidopropyl betaine (EAB);

[0016] The nonionic surfactant N,N-dimethylhexadecylamine oxide (N0B-2);

[0017] The heat-resistant polyacid is trimesic acid;

[0018] The counter ion compound is sodium salicylate;

[0019] The chelating agent is EDTA;

[0020] The formation water contains inorganic salts, which include one or more of sodium chloride, magnesium chloride, sodium sulfate, sodium bisulfate, sodium carbonate, potassium chloride, and calcium chloride.

[0021] The present invention also provides a method for preparing the above-mentioned high-strength self-assembled gel foam oil-displacing agent, comprising the following steps:

[0022] (1) Heat the formation water to 70-90° C., add the ternary copolymer hydrophobic associating polymer, stir to dissolve, then add the zwitterionic surfactant, stir to dissolve;

[0023] (2) adding a nonionic surfactant and a chelating agent to the mixed solution obtained in step (1) in sequence, stirring and dissolving;

[0024] (3) Add the heat-resistant polyacid and the counterion compound to the mixed solution obtained in step (2), stir and dissolve, and obtain the product.

[0025] The present invention also provides a method for using the high-strength self-assembling gel foam oil-displacing agent, which is as follows:

[0026] A high-strength self-assembled gel foam oil-displacing agent is used to prepare foam through a sand-filled tube model. The specific operation is as follows: the high-strength self-assembled gel foam oil-displacing agent is added into a piston container; the lower end of the piston container is connected to a double-cylinder pump, the upper end of the piston container is connected to the inlet end of the sand-filled tube through a three-way valve, and a nitrogen high-pressure gas cylinder is connected to the inlet end of the sand-filled tube through a three-way valve; the outlet end of the sand-filled tube is connected to a soap bubble flowmeter and a foam test tube in sequence; a high-pressure nitrogen gas cylinder is used to access the upper space of the piston container, fill it with nitrogen gas and keep it isobaric with the high-pressure gas cylinder; the output flow rate of the double-cylinder pump is 1 mL / min, and the gas-liquid ratio is alternately injected at 3:1. After continuous, stable, rich and delicate foam is generated, the injectable high-strength self-assembled foam can be obtained; wherein, the sand-filled tube is filled with quartz sand of 80-100 mesh, and the double-cylinder pump is an ISCO constant pressure and constant flow double-cylinder pump.

[0027] The high-strength self-assembled gel foam oil-displacing agent was injected into a full-size core (L×d=300mm*100mm) for oil displacement experiments. The full-size core was installed vertically with the inlet at the bottom and the outlet at the top. The full-size core is prepared by laser engraving the carbonate outcrop of the fracture-cavity based on the characteristics of the fracture-cavity reservoir, the cave and pore characteristics. The specific operation is as follows: under certain high temperature and high pressure conditions, the full-size core saturated with high-mineralization formation water is placed in a vertical core holder and installed, and confining pressure is applied to check the sealing of the system. If the sealing is good, the experiment is continued; crude oil is injected into the core through an intermediate container until all the outlets are filled with crude oil, and the original oil saturation is established; the water drives the crude oil to the economic limit (the water content is stabilized to 98%), a water-drive reservoir model is established, and the water-drive recovery factor is calculated; the valve is opened, the foam prepared by the sand filling pipe is connected, and the 0.5PV high-strength self-assembled foam is used to displace the crude oil. After the foam segment plug is fully injected, the subsequent water drive is carried out to the economic limit, and the high-strength self-assembled gel foam oil displacement agent is calculated to improve the crude oil recovery factor.

[0028] In the formula of the high-strength self-assembled gel foam oil-displacing agent system described in the present invention, the hydrophobic groups of the ternary amphiphilic hydrophobically associating copolymer are mutually associated to enhance the spatial network structure of the polymer molecules in the solution, so that the polymer viscosity is increased. At the same time, the positive charge in the ternary amphiphilic hydrophobically associating copolymer and the negative charge of the ionized carboxyl group in the polyacid trimesic acid can produce a strong electrostatic interaction, and the electrostatic interaction shortens the relative distance of the hydrophobic groups on different molecular chains, enhances the hydrophobic association between the molecular chains, and makes it easier for the polymer to form a spatial network structure in the solution, thereby improving its viscosity-increasing effect. In addition, the addition of erucic acid amide betaine amphoteric surfactant and N, N-dimethyl hexadecylamine oxide nonionic surfactant first promotes the association of the polymer, so that the viscosity is further increased. The main reason is that the ternary amphiphilic hydrophobically associating polymer forms a hydrophobic micro-region through its own hydrophobic action, and the addition of a low-mass concentration surfactant interacts with the hydrophobic micro-region to form a mixed micelle, which promotes the aggregation between the associated molecules, and the macroscopic performance is an increase in viscosity. In addition, the erucamide betaine amphoteric surfactant can self-assemble to form a composite worm-like micelle under the action of the counterion compound sodium salicylate, and the outline length of this composite worm-like micelle can be from 1000 nanometers to even 100 micrometers; in the solution, when the composite worm-like micelle reaches a certain length and density, the micelles begin to entangle and overlap with each other to form a viscoelastic network structure, and the addition of the ternary copolymer makes this mutual entanglement and overlap more intense. Therefore, it can be seen that there are the following four interactions between the molecules in the foaming agent solution: 1) the ternary amphiphilic hydrophobic associating copolymer itself has a hydrophobic associating effect; 2) the ternary amphiphilic hydrophobic associating copolymer and the polyacid have an electrostatic effect; 3) the ternary amphiphilic hydrophobic associating copolymer and the surfactant form mixed micelles to promote the association and aggregation of polymer molecules; 4) the erucamide betaine amphoteric surfactant and the counterion compound sodium salicylate self-assemble to form a composite worm-like micelle, and the micelles entangle with each other to form a viscoelastic network structure. Under these four interactions between molecules, the viscosity of the foaming system increases a lot under high temperature conditions.

[0029] Different from the existing polymer solutions, the polymer prepared in the present invention is a long-chain molecular structure linked together by covalent bonds, while the foaming agent system has association between macromolecules, electrostatic interaction between macromolecules and small molecules, and molecular ordered assemblies formed by the aggregation of small molecules under the action of intermolecular forces. The molecular ordered assemblies are entangled with the polymer to form a complex.

[0030] The present invention adopts an association structure, a composite worm-like micelle structure, an aggregation structure, an entanglement structure formed by a ternary amphiphilic hydrophobic associating copolymer, a surfactant molecule, a polyacid and a sodium salicylate counterion, and there is a process of dissociation and recombination. Therefore, the whole system is a dynamic and balanced network structure.

[0031] Compared with the invention patents CN110776893A and ZL201710864250.3, the counterion molecular weight of the present invention is small, and the composite worm-like micelles formed by self-assembly are longer. The viscosity is higher at the same dosage in the macroscopic view, and the concentration required to form worm-like micelles of the same length is greatly reduced by compounding with the hydrophobic associating polymer of the terpolymer, thereby reducing the dosage of the surfactant. Since the formation of the composite worm-like micelles can effectively prevent the formation of calcium carbonate nuclei and the growth of crystals, the calcium and magnesium ions squeeze the composite worm-like micelles to cause the double electric layer to become thinner, the fluid mechanics of the composite worm-like micelles is reduced, the scale is reduced, and the foam produced is small, uniform, and has good stability. At the same time, the synergistic effect of the erucamide betaine surfactant and the amine oxide type nonionic surfactant causes the surfactant molecules to be arranged more closely at the oil-water interface, and the oil-water interfacial tension is reduced more strongly, which can make the oil-water interfacial tension value reach an ultra-low value. In addition, the erucamide betaine surfactant, N,N-dimethyl hexadecylamine oxide nonionic surfactant and the dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC) monomer unit in the ternary amphiphilic hydrophobic associating copolymer all have long-chain hydrophobic groups, which are beneficial to enhancing the hydrophobic association. Benzoic acid and the dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC) monomer unit in the ternary amphiphilic hydrophobic associating copolymer are beneficial to improving the temperature resistance of the foaming liquid. Erucamide betaine surfactant, N,N-dimethyl hexadecylamine oxide nonionic surfactant and the ternary amphiphilic hydrophobic associating copolymer can significantly improve the salt resistance of the foaming liquid.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The foam oil-displacing agent of the present invention has four kinds of interactions between the molecules of the ternary copolymer hydrophobic associating polymer, erucic acid amide propyl betaine, trimesic acid and sodium salicylate in salt water, and can form a multi-layered complex with higher viscosity. Under the same conditions, the viscosity of the system formed by sodium salicylate is much greater than that of the system formed by sodium dodecyl sulfate; the viscosity of the system formed by trimesic acid is much greater than that of the system formed by glutaric acid. When nitrogen is introduced and foamed, the foam produced is rich, delicate and has a long half-life. When nitrogen foam is injected into the high-temperature and high-salt fracture-cavity oil reservoir of the Northwest Oilfield, it is both salt-resistant and temperature-resistant. The foam system will not precipitate with calcium and magnesium ions, and has good foaming and foam stability, and can also make the oil-water interfacial tension reach the order of 10-3mN / m.

[0034] (2) The foam oil displacement agent of the present invention does not contain alkali, thus avoiding the problems of reducing the viscoelasticity of the system, precipitation between alkali and formation water, increasing the difficulty of injection process and produced fluid treatment, and increasing costs caused by alkali in application. At the same time, the addition of terpolymer improves the viscosity-increasing ability of the foam liquid under high temperature conditions. The hydraulic radius of the random coil formed after dissolving in formation water is large, reflecting high viscosity and thick foam liquid film, which can effectively block caves and large cracks in fracture-cavity oil reservoirs;

[0035] (3) The foam stability after foaming is significantly improved, which improves the fluidity of the oil-water two-phase, expands the swept volume, significantly reduces the oil-water interfacial tension, improves the oil washing efficiency and increases the formation energy, and improves the seepage capacity of the oil phase liquid, thereby significantly improving the crude oil recovery rate of high-temperature and high-salt fracture-cavity reservoirs. DETAILED DESCRIPTION

[0036] Example 1 A high-strength self-assembled gel foam oil-displacing agent and its preparation method

[0037] It is composed of the following components in weight percentage:

[0038]

[0039] The ternary amphiphilic hydrophobically associating copolymer is obtained by copolymerization of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC), and the mass ratio of the monomer units of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC) is 5:1:0.1.

[0040] The mineralization of the formation water is:

[0041] Sodium ion Potassium Calcium Magnesium ion Chloride ion Bicarbonate ion Total mineralization mg / L 40452.5 13315 10665 8042.5 88242.5 3135.0 163852.5

[0042] Preparation method:

[0043] (1) Heat the formation water to 80° C., add the ternary copolymer hydrophobic associating polymer, stir to dissolve, then add erucamidopropyl betaine, stir to dissolve;

[0044] (2) adding a nonionic surfactant N,N-dimethylhexadecylamine oxide and a chelating agent to the mixed solution obtained in step (1) in sequence, stirring and dissolving;

[0045] (3) Add trimesic acid and sodium salicylate to the mixed solution obtained in step (2), stir and dissolve to obtain the product.

[0046] Example 2 A high-strength self-assembling gel foam oil-displacing agent and its preparation method

[0047] It is composed of the following components in weight percentage:

[0048]

[0049] The ternary amphiphilic hydrophobically associating copolymer is obtained by copolymerization of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC), and the mass ratio of the monomer units of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC) is 6:1:0.3.

[0050] The mineralization of the formation water is:

[0051] Sodium ion Potassium Calcium Magnesium ion Chloride ion Bicarbonate ion Total mineralization mg / L 50161.1 16510.6 13224.6 9972.7 109420.7 3887.4 203177.1

[0052] Preparation method:

[0053] (1) Heat the formation water to 80° C., add the ternary copolymer hydrophobic associating polymer, stir to dissolve, then add erucamidopropyl betaine, stir to dissolve;

[0054] (2) adding a nonionic surfactant N,N-dimethylhexadecylamine oxide and a chelating agent to the mixed solution obtained in step (1) in sequence, stirring and dissolving;

[0055] (3) Add trimesic acid and sodium salicylate to the mixed solution obtained in step (2), stir and dissolve to obtain the product.

[0056] Example 3 A high-strength self-assembled gel foam oil-displacing agent and its preparation method

[0057] It is composed of the following components in weight percentage:

[0058]

[0059]

[0060] The ternary amphiphilic hydrophobically associating copolymer is obtained by copolymerization of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC), and the mass ratio of the monomer units of acrylamide (AM), methacryloyloxyethyl-N,N-dimethylpropane sulfonate (DMAPS), and dioctadecyl methyl allyl ammonium chloride (DiC18DMAAC) is 4:0.5:0.2.

[0061] The mineralization of the formation water is:

[0062] Sodium ion Potassium Calcium Magnesium ion Chloride ion Bicarbonate ion Total mineralization mg / L 55015.4 17108.4 14165.0 10437.8 119009.8 4263.6 220000.0

[0063] Preparation method:

[0064] (1) Heat the formation water to 80° C., add the ternary copolymer hydrophobic associating polymer, stir to dissolve, then add erucamidopropyl betaine, stir to dissolve;

[0065] (2) adding a nonionic surfactant N,N-dimethylhexadecylamine oxide and a chelating agent to the mixed solution obtained in step (1) in sequence, stirring and dissolving;

[0066] (3) Add trimesic acid and sodium salicylate to the mixed solution obtained in step (2), stir and dissolve to obtain the product.

[0067] Performance Testing:

[0068] 1. Viscosity, interfacial tension, foamability and half-life testing of foam oil displacement agents under high temperature and high pressure

[0069] Test method:

[0070] (1) The viscosity of the foam oil-displacing agent prepared in Examples 1-3 was measured at a temperature of 150° C. and a pressure of 40 MPa using a high-temperature and high-pressure HAKEE rheometer, and the oil-water interfacial tension was measured at a temperature of 150° C. and a pressure of 40 MPa using a high-temperature and high-pressure Tax500 ultra-low rotation interfacial tension meter. The results are shown in Table 1.

[0071] (2) 200 mL of the foam oil-displacing agent prepared in Examples 1-3 above was placed in a high-temperature and high-pressure visual foaming device (Patent No. ZL201010130488.1), the stirring device was sealed, nitrogen was introduced, the temperature was raised to 150° C., the pressure was increased to 40 MPa, and the mixture was stirred at a speed of 4000 rpm for 60 s. The initial foam volume V0 was immediately read and timing was started; the time t required for half of the foam to disappear was recorded. 1 / 2 , which is the foam half-life, and finally calculate the foam comprehensive index FCI (FCI = 0.75 × V0 × t 1 / 2 ).

[0072] Table 1 Effect of viscosity, interfacial tension, foaming property and half-life of foam flooding agent under high temperature and high pressure

[0073]

[0074] Compared with the invention patent ZL201710864250.3, the present invention does not use triethanolamine and urea; compared with the corresponding embodiment of the invention patent ZL201710864250.3, the viscosity and foam comprehensive index FCI of the foam oil displacement agent in Examples 1, 2 and 3 of the present invention are significantly increased.

[0075] According to the test data in Table 1 above, the oil-water interfacial tension of the three embodiments of the invention patent ZL201710864250.3 is less than 10 -3 mN.m -1 The oil-water interfacial tension of Examples 1 and 2 of the present invention both reached 10 - 3 mN.m -1 Therefore, the oil-displacing agent of the present invention is more effective in reducing the oil-water interfacial tension.

[0076] When the total amount (0.66-1.36%) of the main agent used in the present invention (including ternary copolymer hydrophobic associating polymer, erucic acid amidopropyl betaine, N,N-dimethyl hexadecylamine oxide, trimesic acid, sodium salicylate, chelating agent EDTA) is much smaller than the total amount (30-80%) of the main agent (anionic and cationic surfactants, betaine-type surfactants and nonionic surfactants) of the invention patent CN110776893A, compared with the 9 embodiments of the invention patent ZL 201810856435.4, ZL 201810856435.4 does not have any half-life data, which is seriously missing. After repeated tests, it is determined that its half-life is only 3-5min, which is much lower than the data 17-22min in the above table of the present invention. Therefore, the foam comprehensive index value of the present invention is larger, the self-assembly ability is stronger, and the comprehensive foam performance is better.

[0077] 2. The foam oil displacement agent prepared by the present invention is used to prepare foam through a sand filling pipe, and then injected into a full-size core to detect its crude oil recovery rate.

[0078] The specific operation is as follows: adding a high-strength self-assembled gel foam oil-displacing agent into a piston container; the lower end of the piston container is connected to a double-cylinder pump, the upper end of the piston container is connected to the inlet end of the sand-filling tube through a three-way valve, and a nitrogen high-pressure gas cylinder is connected to the inlet end of the sand-filling tube through a three-way valve; the outlet end of the sand-filling tube is connected to a soap bubble flowmeter and a foam test tube in sequence; a nitrogen high-pressure gas cylinder is connected to the upper space of the piston container, filled with nitrogen gas and maintained at the same pressure as the nitrogen high-pressure gas cylinder; the output flow rate of the double-cylinder pump is 1 mL / min, and the gas-liquid ratio is alternately injected at 3:1. After a continuous, stable, rich and delicate foam is produced, a high-strength self-assembled foam that can be injected into a full-size core can be obtained; wherein, the sand-filling tube is filled with quartz sand of 80-100 mesh, and the double-cylinder pump is an ISCO constant pressure and constant flow double-cylinder pump;

[0079] The high-strength self-assembled gel foam oil-displacing agent was injected into a full-size core (L×d=300mm*100mm) for oil displacement experiments. The full-size core was installed vertically with the inlet at the bottom and the outlet at the top. The full-size core is prepared by laser engraving the carbonate outcrop of the fracture-cavity based on the characteristics of the fracture-cavity reservoir, the cave and pore characteristics. The specific operation is as follows: under certain high temperature and high pressure conditions, the full-size core saturated with high-mineralization formation water is placed in a vertical core holder and installed, and confining pressure is applied to check the sealing of the system. If the sealing is good, the experiment is continued; crude oil is injected into the core through an intermediate container until all the outlets are filled with crude oil, and the original oil saturation is established; the water drives the crude oil to the economic limit (the water content is stabilized to 98%), a water-drive reservoir model is established, and the water-drive recovery factor is calculated; the valve is opened, the foam prepared by the sand filling pipe is connected, and the 0.5PV high-strength self-assembled foam is used to displace the crude oil. After the foam segment plug is fully injected, the subsequent water drive is carried out to the economic limit, and the high-strength self-assembled gel foam oil displacement agent is calculated to improve the crude oil recovery factor.

[0080] The core parameters of the cores used in Examples 1-3 are shown in Table 2, and the displacement test results of the high-strength self-assembled gel foam oil displacement agent used in Examples 1-3 are shown in Table 3.

[0081] Table 2 Basic parameters of the full-diameter fracture-cavity core used in the experiment

[0082]

[0083] Table 3 High-strength self-assembled foam flooding experimental results

[0084] Core number Water drive efficiency / % <![CDATA[Stable flow differential pressure / Mpa.m -1 > Foam flooding to improve oil recovery / % Example 1 43.14 3.1 24.7 Example 2 40.76 3.4 26.8 Example 3 38.66 3.6 29.3

[0085] According to the test data in Table 3 above, the foam system prepared by the main agent used in the present invention (including ternary amphiphilic hydrophobic associating copolymer, erucic acid amidopropyl betaine, N,N-dimethyl hexadecylamine oxide, trimesic acid, sodium salicylate, and chelating agent EDTA) has an increased recovery rate of 24.7%, 26.8% and 29.3% in the above three embodiments, respectively. The oil displacement efficiencies in embodiments 1 to 9 of the invention patent ZL201810856435.4 are 16.2%, 20.5%, 18.9%, 17.3%, 18.1%, 18.5%, 19.1%, 20.7% and 18.8%, respectively. The minimum oil displacement efficiency and the maximum oil displacement efficiency of the oil displacement agent of the present invention are 8.5% and 8.6% higher, respectively, and thus have a higher oil displacement capacity.

[0086] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A high-strength self-assembled gel foam oil-displacing agent, characterized in that: It is composed of the following components in weight percentage: The remainder is formation water. The mineralization of the formation water is 100,000-300,000 mg / L.

2. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The ternary amphiphilic hydrophobic associating copolymer is obtained by copolymerizing acrylamide, methacryloyloxyethyl-N,N-dimethylpropanesulfonate and dioctadecyl methylallyl ammonium chloride.

3. The high-strength self-assembling gel foam oil-displacing agent according to claim 2, characterized in that: The mass ratio of acrylamide, methacryloyloxyethyl-N,N-dimethylpropanesulfonate and dioctadecyl methylallyl ammonium chloride monomer units in the ternary amphiphilic hydrophobically associating copolymer is 4-6:0.5-1:0.1-0.

3.

4. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The zwitterionic surfactant is erucamidopropyl betaine.

5. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The nonionic surfactant is N,N-dimethylhexadecylamine oxide.

6. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The heat-resistant polyacid is trimesic acid.

7. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The counter ion compound is sodium salicylate.

8. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The chelating agent is EDTA.

9. The high-strength self-assembling gel foam oil-displacing agent according to claim 1, characterized in that: The formation water contains inorganic salts, which include one or more of sodium chloride, magnesium chloride, sodium sulfate, sodium bisulfate, sodium carbonate, potassium chloride, and calcium chloride.

10. The method for preparing the high-strength self-assembling gel foam oil-displacing agent according to any one of claims 1 to 9, characterized in that: The steps include: (1) Heat the formation water to 70-90° C., add the ternary copolymer hydrophobic associating polymer, stir to dissolve, then add the zwitterionic surfactant, stir to dissolve; (2) adding a nonionic surfactant and a chelating agent to the mixed solution obtained in step (1) in sequence, stirring and dissolving; (3) Add the heat-resistant polyacid and the counterion compound to the mixed solution obtained in step (2), stir and dissolve, and obtain the product.

Citation Information

Patent Citations

  • High-temperature, high-pressure, and acid-resisting apparatus for foam generation and dynamic evaluation

    CN102192864B

  • A self-assembled ultra-micro foam oil displacement agent, its preparation method and application

    CN107502330B

  • A low interfacial tension, high-strength foam displacement agent

    CN110776893B

  • Self-assembled ultramicro-foam oil-displacing agent as well as preparation method and application thereof

    CN107502330A

  • Low-interfacial-tension strong-foam oil-displacing agent

    CN110776893A